2007
DOI: 10.1103/physrevlett.99.026102
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Depolarized ZnO(0001) Monolayers: Formation of Unreconstructed Planar Sheets

Abstract: A novel nonpolar structure of 2 monolayer (ML) thick ZnO(0001) films grown on Ag(111) has been revealed, using surface x-ray diffraction and scanning tunneling microscopy. Zn and O atoms are arranged in planar sheets like in the hexagonal boron-nitride prototype structure. The observed depolarization is accompanied by a significant lateral 1.6% expansion of the lattice parameter and a 3% reduced Zn-O bond length within the sheets. The nonpolar structure stabilizes an atomically flat surface morphology unseen f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

64
518
7
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 692 publications
(592 citation statements)
references
References 19 publications
64
518
7
3
Order By: Relevance
“…However, our studies of FeO(111) [10] and ZnO(0001) [13] films on Pt(111) showed that such a monolayer structure is unstable under realistic pressure conditions. Moreover, other DFT studies of ZnO(0001) films on noble metals (Pd(111) [35], Cu(111) [36], and Au(111) [37]) and experimental data available for ZnO/Ag(111) [21] revealed substantial interlayer relaxations such that ultrathin ZnO films resemble the co-planar sheets in the boron nitride (or graphite) structure, and they are only weakly bound to a metal support, in contrast to the models used by Sun et al [34].…”
Section: Reactivity Of Metal-supported Zno(0001) Films: Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our studies of FeO(111) [10] and ZnO(0001) [13] films on Pt(111) showed that such a monolayer structure is unstable under realistic pressure conditions. Moreover, other DFT studies of ZnO(0001) films on noble metals (Pd(111) [35], Cu(111) [36], and Au(111) [37]) and experimental data available for ZnO/Ag(111) [21] revealed substantial interlayer relaxations such that ultrathin ZnO films resemble the co-planar sheets in the boron nitride (or graphite) structure, and they are only weakly bound to a metal support, in contrast to the models used by Sun et al [34].…”
Section: Reactivity Of Metal-supported Zno(0001) Films: Comparisonmentioning
confidence: 99%
“…The oxides formed at 300 K showed no long-range order, but upon heating to 500 K surface structures analogous to the polar surfaces of bulk ZnO (0001) were observed. Well-ordered ZnO films on Ag(111), prepared by pulsed laser deposition and vacuum annealing at 680 K, were used by Tusche et al [21] to provide evidence for a theoretically predicted [22] depolarized ZnO(0001) structure, i.e. where Zn and O atoms are arranged in planar sheets as in the hexagonal boron-nitride structure.…”
Section: Introductionmentioning
confidence: 99%
“…However, firstprinciples calculations [20,21] have predicted and then confirmed experimentally [22] that the ZnO(0001) film prefers a graphitic honeycomb structure as the layer number is reduced. Furthermore, 2D g-ZnO monolayer itself is also semiconducting with a wide band gap of 3.57 eV , showing many interesting electronic and magnetic properties [47][48][49].…”
Section: Introductionmentioning
confidence: 98%
“…Two-dimensional (2D) ultrathin materials, such as graphene [1][2][3], silicene [4][5][6][7], germanene [8][9][10], phosphorene [11][12][13], hexagonal boron nitride (h-BN) [14][15][16], graphitic carbon nitride (g-C 3 N 4 ) [17][18][19], graphitic zinc oxide (g-ZnO) [20][21][22] and molybdenum disulphide (MoS 2 ) [23][24][25], have received considerable interest recently owing to their outstanding properties and wide applications. There already have been many review articles [26][27][28][29][30][31][32] for the research on 2D materials over the past several years.…”
Section: Introductionmentioning
confidence: 99%
“…27 Dong and coworkers recently predicted that boron phosphide and silicon carbide nanoribbons can be used in the fabrication of promising nanoelectronic and spintronic devices. 28 Motivated by recent experiments demonstrating the successful synthesis of monolayers of III-V binary compounds 29,30 and theoretical work 27 reporting the stability of such materials, we investigated the electronic and transport properties of doped h-BP, by firstly examining the mechanical stability of the pristine structure. Furthermore, we propose the utilization of h-BP for the construction of a p-n junction.…”
Section: Introductionmentioning
confidence: 99%